Finance-growth nexus and the role of institutions in mitigating push and pull factors - Murdipi, Rafiqa (2019)
The rises of financial fragility and fluctuation of capital flows and increases of global uncertainty in last couple of decades motivate this study to examine the interrelationships between global and domestic uncertainty, financial and capital flow stability and economic growth. There are three specific objectives in this thesis. First, to examine the spillover effect of global uncertainty shocks on domestic financial performance and the finance-growth nexus. Second, to investigate the role of regimes of push and pull factors in explaining the gains and losses of capital flows on growth. Lastly, to examine the role of institutions in mitigating the risks of push and pull factors on economic growth. Firstly, a reduction in significant positive effect of financial development on economic growth that is documented in recent studies of finance-growth literature motivate this present study to examine driven factors of global uncertainty in distorting financial development and hence explaining the reduction of financial performance on economic growth. By employing panel vector autoregressive (Panel VAR) of a sample of 86 countries over the period 1990 to 2015, our empirical results show that global uncertainty shock significantly causes a drop in financial development. Further, this study examines the indirect effect of global uncertainty on the finance-growth nexus by examining the relationship between financial development and economic growth based on regimes of global uncertainty. Our results demonstrate that financial development has a statistically significant positive effect on economic growth during low regime of global uncertainty, but has insignificant effect on economic growth especially during a period of high global uncertainty. Secondly, the puzzle of gains and losses of financial openness is still an ongoing debate until today. While most existing literature examine the direct effect of financial openness on growth, there are less attempts to investigate potential factors that drive and explained the puzzle and mixed results of financial openness on growth. To fill the gap, for our second objective, this study examines the significant role of push and pull factors which consist of components such as global uncertainty and domestic risk inflation uncertainty in influencing the effects of financial openness on economic growth. Based on the panel threshold method, our results indicate that the impact of capital flows on economic growth varies, and relies on the regimes of push and pull factors. In other words, the puzzle of cost and benefits of financial openness can be explained by the uncertainty levels of global and domestic factors. Financial openness can bring benefits to economic growth when the global environment is at low uncertainty, with high liquidity and high interest rate as well as stable macroeconomic factors of low inflation uncertainty, and low public debt. Lastly, the important role of institutions in mitigating the risk of push and pull factors on economic growth is examined in this study. The experience of the 2008 Global Financial Crisis has motivated many countries to scrutinize and find effective strategies to increase resilience towards the risks from both global and domestic macroeconomic factors to prevent them from the adverse effects of financial instability and growth collapse. Our empirical analyses suggest that good quality institutions especially political institutions are fundamental elements in helping countries (particularly the emerging/developing countries) to alleviate the severe spillover risks of global factors and increase sustainability of domestic factors for maintaining growth and reducing the cost of financial integration.